Шлифовальные круги с функционально-ориентированным рабочим слоем из СТМ - Шепелев, А.А.; Сороченко, В.Г.; Дуброва, А.Е.; Шепелев, А.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
High-efficiency abrasive wheels with the is functional-focused working layer from SHМ are considered in article. Laws of processes of grinding of hard alloys, hard alloys in common with steel on metal and organic bonds are presented. And also processes of cutting of composite and other building materials by disk tools from SHМ on a metal bond.